Activation of Water‐Splitting Photocatalysts by Loading with Ultrafine Rh–Cr Mixed‐Oxide Cocatalyst Nanoparticles. (6th March 2020) - Kurashige, Wataru; Mori, Yutaro; Ozaki, Shuhei; Kawachi, Masanobu; Hossain, Sakiat; Kawawaki, Tokuhisa; Shearer, Cameron J.; Iwase, Akihide; Metha, Gregory F.; Yamazoe, Seiji; Kudo, Akihiko; Negishi, Yuichi
Abstract: The activity of many water‐splitting photocatalysts could be improved by the use of Rh III –Cr III mixed oxide (Rh2− x Cr x O3 ) particles as cocatalysts. Although further improvement of water‐splitting activity could be achieved if the size of the Rh2− x Cr x O3 particles was decreased further, it is difficult to load ultrafine (<2 nm) Rh2− x Cr x O3 particles onto a photocatalyst by using conventional loading methods. In this study, a new loading method was successfully established and was used to load Rh2− x Cr x O3 particles with a size of approximately 1.3 nm and a narrow size distribution onto a BaLa4 Ti4 O15 photocatalyst. The obtained photocatalyst exhibited an apparent quantum yield of 16 %, which is the highest achieved for BaLa4 Ti4 O15 to date. Thus, the developed loading technique of Rh2− x Cr x O3 particles is extremely effective at improving the activity of the water‐splitting photocatalyst BaLa4 Ti4 O15 . This method is expected to be extended to other advanced water‐splitting photocatalysts to achieve higher quantum yields. Abstract : Rh2− x Cr x O3 Partikel mit einer Größe von etwa 1, 3 nm wurden auf einen BaLa4 Ti4 O15 ‐Photokatalysator geladen. Der Photokatalysator zeigte die höchste Quantenausbeute, die bisher für BaLa4 Ti4 O15 berichtet wurde. Es wird erwartet, dass die entwickelte Technik zur Herstellung der Rh2− x Cr x O3 ‐Partikel auch die Aktivität anderer Photokatalysatoren zur Wasserspaltung verbessern wird. SG=Glutathionat.